Genetic diet interactions of ACE: the increased hypertension predisposition in the Latin American population - Zambrano, Ana Karina; Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Ruiz-Pozo, Viviana A.; Tamayo-Trujillo, Rafael; Paz-Cruz, Elius; Ibarra-Rodríguez, Adriana Alexandra; Doménech, Nieves (Frontiers in Nutrition, 2023)
Hypertension is one of the primary risk factors associated with cardiovascular diseases (CVDs). It is a condition that affects people worldwide, and its prevalence is increasing due to several factors, such as lack of physical activity, population aging, and unhealthy diets.Notably, this increase has primarily occurred in low and middle-income countries (LMICs). In Latin America, approximately 40% of adults have been diagnosed with hypertension.Moreover, reports have shown that the Latin American genetic composition is highly diverse, and this genetic background can influence various biological processes, including disease predisposition and treatment effectiveness.Research has shown that Western dietary patterns, which include increased consumption of red meat, refined grains, sugar, and ultra-processed food, have spread across the globe, including Latin America, due to globalization processes. Furthermore, a higher than recommended sodium consumption, which has been associated with hypertension, has been identified across different regions, including Asia, Europe, America, Oceania, and Africa.In conclusion, hypertension is a multifactorial disease involving environmental and genetic factors. In Latin America, hypertension prevalence is increasing due to various factors, including age, the adoption of a "Westernized" diet, and potential genetic predisposition factors involving the ACE gene. Furthermore, identifying the genetic and molecular mechanisms of the disease, its association with diet, and how they interact is essential for the development of personalized treatments to increase its efficacy and reduce side effects.